De-identified linkage of data across separate registers: a proposal for improved protection of personal information in registry-based clinical research. (2nd January 2019) - Snäckerström, Tomas; Johansen, Christian
Abstract: Over the last decades the advent of digital documentation has provided research communities with valuable resources of information for clinical research. To utilize the potential of information about patients, their health care, and its outcome that is already available in different registers, the possibility to cross-reference information from different registers is inevitably required. When performing linkage, we are currently forced to disclose information of participating subjects either to the administration of the other register(s) or to the researcher. Considering the increased concern of issues around personal integrity, this is a limitation that affects the ethical implications of proposed research and that might in the end affect the willingness of subjects to participate in registers. For this reason we propose a different methodology for performing cross-referencing, one that effectively prevents information leakage between the different organizations participating in linking the data. We believe that it is possible to use commonly adopted technologies within the area of data security and encryption to perform linkage without disclosing any sensitive information between different participants. In this paper we demonstrate how common techniques of encryption could be implemented to achieve that and furthermore significantly simplify discovery and feasibility surveying ahead of studies.